Enhanced thermoelectric performance of In-doped and AgCuTe-alloyed SnTe through band engineering and endotaxial nanostructures. Issue 44 (4th November 2022) - Peng, Panpan; Wang, Chao; Li, Lanwei; Li, Shuyao; Chen, Jing; Fan, Pengya; Du, Rui; Si, Haotian; Cheng, Zhenxiang; Wang, Jianli
Abstract : AgCuTe alloying introduces endotaxial nanostructures in SnTe, which significantly decrease thermal conductivity and enhance ZT . Abstract : Endotaxial nanostructures can reduce lattice thermal conductivity through enhancing phonon scattering without affecting electrical transport, leading to a high thermoelectric performance. On the other hand, band engineering can enhance electrical transport by improving the Seebeck coefficient through valence band convergence and the resonance level. In this paper, the synergistic effect of band engineering and endotaxial nanostructures was implemented in SnTe thermoelectric materials by alloying with AgCuTe and doping with Indium. The positron annihilation lifetime spectra show that the vacancy concentration in SnTe was reduced after alloying with AgCuTe, which led to a decreasing hole concentration and improved carrier mobility. Additionally, the diffusion of Ag in the matrix during the preparation can facilitate valence band convergence. Therefore, the power factor of SnTe is greatly increased to 18 μW cm −1 K −2 at 800 K, which can be further increased to 21.4 μW cm −1 K −2 at 800 K after In doping due to resonance level formation. Meanwhile, Cu2 Te endotaxial nanostructures also can be observed in the TEM image after SnTe alloying with AgCuTe. So, the lattice thermal conductivity significantly reduced to 0.93 W m −1 K −1 in In-doped and AgCuTe-alloyed SnTe. Finally, we obtain an enhanced ZT value of 1.14 in Sn1.02 In0.01 Te–1%AgCuTe at 800 K.